An approach to separating Pu, U, and Ti from high-purity graphite for isotopic analysis by MC-ICP-MS. Issue 6 (26th April 2021) - Metzger, Shalina C.; Manard, Benjamin T.; Bostick, Debra A.; Ticknor, Brian W.; Rogers, Kayron T.; McBay, Eddy H.; Glasgow, David C.; Zirakparvar, N. Alex; Hexel, Cole R.
Abstract : Purification of plutonium, uranium, and titanium from high-purity graphite for high precision isotopic analysis via MC-ICP-MS. Abstract : Information about elemental and isotopic systematics of ultra-trace level actinides ( e.g. U and Pu) and main group elements ( e.g. Ti) present within nuclear grade graphite is vital to the nuclear community for improved reactor operation and security. In support of this, extensive effort has been placed on improving analysis methods ( i.e., inductively coupled plasma-mass spectrometry). However, significantly less effort has been devoted to the optimization of chemical separation methods. Within the separation community, commercially available Eichrom™ resins are often employed, as their elution characteristics for various elements have been well studied, but the direct optimization of actinides and trace metal separations from a single sample have not been widely investigated. Here, methods using various Eichrom pre-packed cartridges were explored to achieve separation of ultra-trace levels of U, Pu, and Ti from a variety of graphite samples. Once the validity of the combined separation scheme was established using certified reference materials, the method was applied to historic, unirradiated and irradiated, graphite samples. For all samples investigated, precise isotope ratio measurements for the titanium isotope systems were made.